PHYTOCHEMICAL STUDIES AND HIGH-PERFORMANCE THIN-LAYER CHROMATOGRAPHY ANALYSIS OF CALAMUS ROTANG LINN LEAF EXTRACTS - Y, Pallavi; Kpj, Hemalatha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present study was aimed at phytochemical screening, quantification, and high-performance thin-layer chromatography (HPTLC) analysis of hexane, chloroform and ethanol leaf extracts of Calamus rotang. Methods: Leaf extracts were prepared according to the polarity of the solvents, i.e., hexane, chloroform, and ethanol. Preliminary phytochemical screening involved the qualitative methods to detect the presence of alkaloids, phenols, flavonoids, saponins, steroids, etc. Quantitative estimation of alkaloids using boldine as standard, phenols using gallic acid as standard, and flavonoids using quercetin as standard were done. HPTLC analysis was done with all three extracts along with quercetin and rutin standards using mobile phase for flavonoids, i.e., 90:10 ratio of chloroform and methanol solvents. Results: Phytochemical screening showed the presence of phenols, flavonoids, alkaloids, etc. Hence, quantification was done for these phytochemicals. Alkaloids were present significantly more in hexane leaf extract, i.e., 2.54Â±0.216mg boldine equivalents/g. Phenols were present significantly more in ethanolic leaf extract, i.e., 49.04Â±0.364 mg gallic acid equivalents)/g. Flavonoids were present in significant amount in ethanolic leaf extract, i.e., 458.85Â±5.74 mg quercetin equivalents/g. HPTLC analysis of hexane, chloroform, and ethanolic extracts showed the presence of flavonoids such as quercetin, rutin, and some unknown flavonoid compounds. Conclusion: Ethanolic leaf extract showed a high amount of phenols and flavonoids. Hence, the extract can be further exploited further for in vitro and in vivo research work.